The Dirt Deposited on the Medium-Voltage Insulators Used in the Plasma Reactor and the Cylinder-Type Electrostatic Precipitator - Gabriel Nicolae Popa (Applied Sciences)
The plasma reactor and cylindrical-type electrostatic precipitator (PRESP), combined operation in one device, made in the metallic chimney of low-thermal power boilers (up to 50 kW) that burn wood, can be used in home applications. The discharge electrode is stretched and supported by two groups of medium-voltage insulators. The sensitive elements of PRESP are medium-voltage insulators. This article analyses the design, use, and effect of dirty gases on the medium-voltage insulators that support the discharge electrode under real operating conditions for a PRESP installed in a 20 kW thermal power boiler that burns wood (there are no studies on the performance of PRESP). The electrical properties of the medium-voltage insulators (isolation resistance, dielectric absorption ratio, and polarisation index) and the chemical analysis of the dust layer deposited on the medium-voltage insulators are analysed. Of the two types of insulators analysed, a longer length of the electrical insulators determines a safer and better operation of PRESP. After a period of operation of the PRESP, the insulation resistance decreases by more than 10 times. The polarisation index (values greater than 1.1–1.2) provides better information (compared to the dielectric absorption ratio) on the insulation quality.